Agile digital transformation in SMEs: a hybrid prioritization approach - Bayat, Maryam; Hassanzadeh, Alireza; Shayan, Ali; Ostadi, Bakhtiar; Hassani, Hamed (Frontiers in Sustainability, 2025)
IntroductionAgile Digital Transformation (ADT) represents a new generation of digital transformation that enables small and medium-sized enterprises (SMEs) to adopt iterative and data-driven strategies, enhancing their flexibility, competitiveness, and sustainability. Despite extensive research on digital transformation (DT), few studies have explored the specific enablers of ADT tailored to SMEs.MethodsThis study employed a rigorous three-phase methodology, combining a systematic literature review, a hybrid Delphi method involving academic and industry experts, and the Best-Worst Method (BWM) for prioritization.ResultsThe study identified nine key enablers of ADT, organized under four overarching themes: Strategic Capabilities, Human Capabilities, Organizational Capabilities, and Technological Capabilities. The most significant enablers include transformational leadership, agile organizational strategy, and dynamic resource management.DiscussionThese findings provide theory-informed and practical guidance for SME managers to navigate digital transformation under resource constraints. The framework aligns with Sustainable Development Goals (SDG 8 and SDG 9) by promoting economic resilience and innovation-led industrial growth.